Little Legends : Exceptional Men In Black History - Harrison, Vashti; Johnson, Kwesi (New York : Little, Brown and Company, 2019)
Profiles thirty-five prominent men in African American history, including James Armistead Lafayette, Thurgood Marshall, Alvin Ailey, and Leland Melvin.
Includes bibliographical references (pages 82-84).
Keywords: African American men -- Biography; African Americans -- Biography; African American men -- Biography; African Americans -- Biography; Biographies